Al substitution effect on magnetic properties of magnetocaloric material HoB2. (1st February 2022) - Iwasaki, Suguru; Yamamoto, Takafumi D.; Baptista de Castro, Pedro; Terashima, Kensei; Takeya, Hiroyuki; Takano, Yoshihiko
Abstract: We investigate the Al substitution effect for HoB2 to tune the Curie temperature ( T C ). The HoB2− x Al x samples with nominal x ( x nom ) of 0, 0.1, 0.3, and 0.5 are characterized by powder X-ray diffraction measurements, EDS analysis and magnetization measurements. The HoB2− x Al x samples with x nom of 0.1, 0.3, and 0.5 show two ferromagnetic transitions at T C1 of ∼15 K and T C2 of >32 K. The T C1 is identical to the T C of HoB2 and does not change with Al substitution. The T C2 is similar to the T C of HoAl2 and varies with Al content. In an EDS analysis, the inhomogeneous elemental distribution is observed in Al-substituted HoB2, where the Al-rich regions exist. Our results suggest that the Al added to HoB2 does not form a solid solution, but rather leads to the phase segregation into stoichiometric HoB2 and B-substituted HoAl2 . The x nom = 0.5 sample exhibits the maximum |Δ S M ( μ 0 H :5 T→0 T)| of 32.1 J kg K −1 at T C1 and a small kink of |Δ S M | at T C2 . Because the |Δ S M | exhibits a maximum at T C1, stoichiometric HoB2 mainly contributes to the maximum of |Δ S M |. Highlights: The influence of Al substitution was investigated for the magnetocaloric material of HoB2 . The substitution of the Al to HoB2 results in the phase segregation into HoB2 and HoAl2 . In magnetization measurements, two ferromagnetic transitions are observed, which are attributed to HoB2 and HoAl2 . Our results indicate that Al substitution to HoB2 is not a promising strategy to tune T C while maintaining |Δ S M |.